2013
DOI: 10.17305/bjbms.2013.2402
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide as a potential biomarker in inflammatory bowel disease

Abstract: The aim of this study was to investigate changes in serum nitric oxide (NO) concentration in inflammatory bowel diseases (IBD) patients and its use as potential biomarker in differential diagnosis of ulcerative colitis (UC) and Crohn's disease (CD) and in disease activity assessment. In 60 patients of both genders - 30 with ulcerative colitis and 30 with Crohn's disease - and 30 controls serum nitric oxide concentration was determined by measuring nitrite concentration, a stable metabolic product of NO with ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 18 publications
4
55
0
Order By: Relevance
“…Our study [16,17] showed significantly higher serum levels of NO in CD patients compared to UC patients. However, data from previous studies reported no significant differences between these two categories of disease, whereas higher systemic levels of NO in UC compared to CD was found [16,17,26,29] . A significant difference was observed in the NO concentrations between the active and inactive phase of the disease.…”
Section: No and Ibdmentioning
confidence: 77%
See 3 more Smart Citations
“…Our study [16,17] showed significantly higher serum levels of NO in CD patients compared to UC patients. However, data from previous studies reported no significant differences between these two categories of disease, whereas higher systemic levels of NO in UC compared to CD was found [16,17,26,29] . A significant difference was observed in the NO concentrations between the active and inactive phase of the disease.…”
Section: No and Ibdmentioning
confidence: 77%
“…This observation suggests a possible use of serum NO levels for monitoring disease activity in both types of IBD [16,28,29] . While several studies conducted using animal models indicate the deleterious effect of NO, recent studies have shown that NO may also exert a protective effect against colitis [29][30][31][32] . One study conducted using a DSSinduced colitis model found that nitrite administration exerts both preventive and therapeutic effects in colonic inflammation [33] .…”
Section: No and Ibdmentioning
confidence: 85%
See 2 more Smart Citations
“…In certain conditions, NO would produce peroxynitrite contributing to cell cytotoxicity and tissue damage and up-regulation of the inflammatory response. In fact an excess of NO is involved in pathophysiology of numerous diseases, including cardiovascular and metabolic diseases (Omar et al 2016), kidney disease (Orida & Lai 2000), inflammatory bowel disease (Avdagi et al 2013), neurological diseases (Ibragic et al 2012), many tumors (Vannini et al 2015) etc.…”
Section: Introductionmentioning
confidence: 99%